Presentation Of The Seven Last Words Of Christ Composed By Théodore Dubois By The Medan Glorious Singers Choir - Kartini Ruth Maduma Manalu; Eniman Gea; Mastaria Simanjuntak (Jurnal Ilmu Sosial Mamangan, 2024)
Cantata BWV 147 Herz und Mund und Tat und Leben (Heart and mouth, deeds and life) by JS Bach is one of the compositions that is often sung, especially the part "Jesu, Joy of Man's Desiring". This study discusses the presentation of The Seven Last Word of Christ by Théodore Dubois by the Medan Glorious Singers Choir. The research used is qualitative research with analytical descriptive writing methods and using a musicological study approach. The relationship between the soloist (soprano, tenor, and baritone) and the choir is an important part of the performance so that harmony and volume can be properly regulated. The consideration of the conductor in determining the repertoire of the performance and how to organize the whole performance is interesting to study, as well as the accompaniment (keyboard) which is an important part in providing color, dynamics, tempo in realizing the metaphors conveyed through the text. Certain parts from text Seven Words Jesus on the Cross supported with election mature melodies and progressions chords that carry we are at a metaphor that goes beyond trajectory history